La influencia de la afectividad familiar en el comportamiento social de las niñas y niños de 3 a 4 años del nivel inicial II paralelo C de la unidad educativa Marieta de Veintimilla del barrio Motupe de la ciudad de Loja. periodo 2014-2015 - Villavicencio Castillo, Elvia Maria (2016)
This research includes a study on the influence of the Family Affection in the social behavior of children 3 to 4 years of the Initial Level II Parallel C Marieta Educational Unit Veintimilla del Barrio Motupe City Loja. 2014-2015. For which he was raised as a general objective: to establish the incidence of family affection in social behavior. The methods used for the development of investigation work were: methods, scientific, analytic-synthetic, hermeneutical, statistician, the technique used was the observation and Scale an instrument of Psychosocial Development aimed at children to measure social behavior and questionnaire applied to parents to measure the level of emotionality. The studied population consisted of 23 children, 23 parents. With the application of the questionnaire to 23 parents, 100% say that collaborate with the serious problems of their children, mention that their home environment is stable, allowing their children to place in an appropriate environment, which encourages socio-emotional and behavioral development of their children. With the Scale of Psychosocial Behavioral Development was determined that 91% of children in the Education Unit have a satisfactory level of socio-emotional development, which will favor the teaching and allows effective teaching, means that the child is acquiring a mastery of his body and the world around him according to their age, and the remaining 9% have a low level of psychosocial behavior.